Biopolymer-Based Nanocomposite Films: Chitosan/Polycaprolactone Matrix Reinforced with Green-Synthesized Silver NPs - Pekdemir, Sibel Selcuk; Tas, Nilay Akkus; Qader, Ibrahim Nazem; Pekdemir, Mustafa Ersin; Babkir, Karukh Ali; Tas, Recep; Kirbag, Sevda (Springer/Plenum Publishers, 2025)
The synthesis and characterization of Chitosan/Polycaprolactone (CHT/PCL) polymer nanocomposites doped with silver nanoparticles (Ag NPs) were conducted for antimicrobial applications. Ag NPs were synthesized using a green method with Sambucus ebulus L. extract, and the nanocomposites were characterized using scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) analysis, and X-ray diffraction (XRD). The SEM images revealed Ag NPs with an average size of similar to 100 nm, while XRD analysis showed a marked increase in crystallinity with higher Ag NP content, indicating improved structural properties. The antimicrobial activity was assessed against Escherichia coli ATCC 25,322, Staphylococcus aureus ATCC 25,923, and Candida albicans FMC17 using the disk diffusion method. The results demonstrated significant antimicrobial activity, with inhibition zones increasing with Ag NP concentrations, particularly against E. coli and C. albicans. The nanocomposites exhibited a 9 mm inhibition zone for E. coli and 10 mm for C. albicans at 3 wt% Ag NP concentration. However, the activity against S. aureus was less pronounced, particularly at higher Ag NP concentrations, potentially due to nanoparticle aggregation. The inclusion of Ag NPs also enhanced the physical properties of the nanocomposites, including increased swelling degree and gel content, although the shape memory effect was observed to be more prominent in films with lower Ag NP concentrations. Overall, CHT/PCL/Ag NP nanocomposites show promising potential for antimicrobial applications, offering a balance of enhanced antimicrobial activity, improved physical properties, and some limitations in activity against certain bacterial strains.
Keywords: Green synthesis; Chitosan/polycaprolactone; Ag NPs; Polymeric nanocomposites; Antimicrobial